The Relationship of Vaccination Status with Implementation Worship Behavior during the COVID-19 Pandemic in Indonesia - Budi Santoso; Siti Mar'atul Munawaroh; Asri Lestari (Journal of Health Promotion and Behavior, 2021)
Background: COVID-19 pandemic has certainly brought tremendous global impacts in various sectors of life, such as social activities that are becoming increasingly limited. In addition, another impact is the prohibition of the implementation of collective worship of Muslims in Indonesia. The government implements health protocols as the main capital to stop the expansion of the pandemic. In addition, the use of vaccines with great hope as one of the main weapons to control COVID-19. This study aims to analyze the relationship between vaccination status and behavior in the implementation of Ramadan worship during the COVID-19 pandemic in Indonesia.Subjects and Method: A cross-sectional study was conducted in Indonesia from April to May 2021, with the research subjects being members of the Muhammadiyah Disaster Management Center (MDMC). A sample of 746 study subjects was selected for this study. The dependent was worship behavior. The independent variable was vaccination status. The data were analyzed by Chi-square test.Results: Complete vaccination status improved the worship behavior during the COVID-19 pandemic (OR= 1.92; 95% CI= 1.43 to 2.57; p<0.001).Conclusion: Complete vaccination status improves the worship behavior during the COVID-19 pandemic.Keywords: vaccination status, worship behavior, COVID-19Correspondence: Budi santoso. Faculty of Health Sciences, Universitas ‘Aisyiyah Yogyakarta, Jl Ring Road Barat 63 Mlangi Nogotirto Gamping Sleman 55292. Email: sitimaratul08@gmail.com. Phone: +6281919120118.Journal of Health Promotion and Behavior (2021), 06(02): 91-96https://doi.org/10.26911/thejhpb.2021.06.02.01